Multi-mechanism synergistic anti-corrosion and anti-pollution composite protective film structure
Through the composite technology of copper alloy and polymer materials, a multi-mechanical anti-corrosion and anti-fouling composite protective film was prepared, which solved the problems of complex construction and poor adhesion of anti-fouling coatings, and achieved long-term and environmentally friendly marine biological protection effects. It is suitable for Deep sea environment.
Patent Information
- Application Number
- CN202411412728.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-31
Smart Images

Figure CN119220193A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite protective film structure, in particular to a multi-mechanism synergistic anti-corrosion and anti-fouling composite protective film structure. Background Art
[0002] Marine biofouling refers to the adverse accumulation of microorganisms, algae and animals on the surface of structures immersed in seawater. Its formation process is that after being immersed in water, a conditional film is first formed on the surface, then a biofilm is formed, and finally a marine fouling biological community is formed, causing biofouling. Biofouling is extremely harmful to human beings engaged in marine development and production activities. Biofouling will increase the navigation resistance of ships, accelerate metal corrosion, block cooling pipes, affect equipment functions, increase operating costs, etc., and cause an increase in greenhouse gas emissions. Marine biofouling refers to the adverse accumulation of microorganisms, algae and animals on the surface of structures immersed in seawater. Its formation process is that after being immersed in water, a conditional film is first formed on the surface, then a biofilm is formed, and finally a marine fouling biological community is formed, causing biofouling. Biofouling is extremely harmful to human beings engaged in marine development and production activities. Biofouling will increase the navigation resistance of ships, accelerate metal corrosion, block cooling pipes, affect equipment functions, increase operating costs, etc., and cause an increase in greenhouse gas emissions. According to incomplete statistics, the various economic losses caused by fouling organisms in my country each year are as high as 100 billion yuan. The technology related to marine antifouling materials has become one of the many bottlenecks restricting the development of my country's marine economy, the reliability of coastal defense security and future deep-sea exploration.
[0003] The prevention and control of marine fouling organisms has always been a matter of great concern to shipbuilding, marine engineering personnel and biologists. So far, the commonly used method to prevent marine biofouling is to apply antifouling paint. However, antifouling paints also have many defects, such as insufficient antifouling effect and unsatisfactory film strength. Traditional organotin antifouling coatings are banned due to their impact on the ecology. Hydrolysis self-polishing antifouling coatings are also accompanied by the release of antifouling agents or other toxic materials. The dissolution of antifouling resins will also form microplastics in the ocean. Especially in special parts such as seabed doors and seabed grilles. The seabed door is the seawater inlet and outlet of the ship. The seawater flow rate is high, and the organic antifouling coating is very easy to peel off. The current commonly used antifouling coatings cannot achieve the ideal antifouling effect. The hull and the seabed door are painted with antifouling paint at the same time, but when there is no biological attachment on the hull, the paint of the seabed door has expired and has been covered with marine organisms, which will cause the seabed door to be blocked, the water flow will be reduced, and the ship's cooling system will be affected, resulting in safety hazards. Another thing is that the construction of antifouling paint is relatively complicated and cumbersome, which is not conducive to use in emergency applications such as quick repairs.
[0004] As shown in Figure 1, the hull and the seabed door are painted with antifouling paint at the same time. However, when there is no biological attachment on the hull, the paint on the seabed door has become ineffective and is already full of marine organisms. This will cause the seabed door to be blocked, reduce water flow, affect the ship's cooling system, and create safety hazards. Another problem is anti-fouling. The construction of dirty paint is relatively complicated and cumbersome, which is not conducive to use in emergency applications such as quick repairs.
[0005] According to preliminary statistics, there are more than 2,000 marine fouling organisms, and my country's coastal areas The common fouling organisms in the area are: 1. Seaweed: mainly filamentous algae, green laver and other algae; 2. Arthropods: mainly barnacles, including flower barnacles, small sardine barnacles, mountain and sea barnacles, vertical striped barnacles, etc.; 3. Coelenterates: mainly shipworms, branching water maggots, red fern water maggots, fan-shaped water maggots, tube worms, hydrozoans, stinging jellyfish, anemones, etc.; 4. Annelids: mainly shipworms, umbrella-shaped corpse coffins, vortex-shaped sandworms, etc.; 5. External anal animals: mainly grass mosses, crusted bryozoans, flying fire mosses, blood mosses, waterside mosses, rough mosses, etc.; 6. Molluscs: mainly oysters, purple shell vegetables, mussels, mussels, etc.; 7. Back-shell animals: mainly ghost sea squirts, white sea squirts, etc.; 8. Microorganisms: mainly various bacteria, fungi, unicellular algae, etc., which usually move on the surface of underwater objects through mucous membranes.
[0006] Marine biofouling process: Marine biofouling can be divided into three levels: 1 Molecular fouling: refers to the accumulation of inorganic and organic molecules in seawater on the surface of immersed objects; 2 Microfouling: refers to the attachment of microorganisms such as diatoms, microalgae, bacteria, fungi, etc. to the surface of immersed objects; 3 Large fouling: refers to the attachment and growth of large marine fouling animals and plants on the surface of submerged objects. Large marine fouling organisms can be divided into soft fouling organisms (such as sea squirts, hydras, algae, etc.) and hard fouling organisms (such as lime worms, oysters, barnacles, etc.).
[0007] The fouling process of marine organisms is generally divided into four stages: Stage 1: Organic molecules in seawater, such as polysaccharides, proteins, protein hydrolysates and inorganic compounds, gather on the surface of immersed objects to form a conditional film. This process is mainly controlled by physical forces (such as van der Waals forces, electrostatic interactions, Brownian motion, etc.); Stage 2: Single-cell diatoms and fungi in seawater quickly attach to the surface of the above-mentioned conditional film. The attachment process of single-cell diatoms and fungi is a reversible physical process. Next, single-cell diatoms and fungi form a layer of microbial mucus with protozoa, which will promote the further attachment of organisms; Stage 3: The secretions of attached fouling organisms, such as nucleic acids, lipids, proteins, polysaccharides, etc., and the rough surface that has been formed will attract more fouling organisms, such as protozoa, marine bacteria, algae germs, crustacean larvae, etc., forming a very complex biological community; Stage 4: Attachment and growth of algae and larger marine invertebrates. These large fouling organisms can deform and grow quickly and have strong environmental adaptability. 3. Harm of marine biofouling In the development of aquaculture, offshore oil and gas resource development, coastal power plants, marine transportation, and territorial defense, the harm caused by marine biofouling has become more and more obvious, and the economic losses caused are even greater. For example, in 1974, the US Navy spent more than 215 million US dollars on damage caused by biofouling; the metal loss caused by anaerobic corrosion caused by biofouling in the United States is estimated to be worth 5 to 6 billion US dollars each year; in the bays around the world, at least 1.4 billion US dollars are spent each year on preventing marine biofouling. In addition, when the biofouling rate of a ship is 5%, the friction coefficient will increase by 50% and the fuel consumption will increase by 40-50%. For example, if 10% of the surface of a 10,000-ton ocean-going ship is fouled by marine organisms, it can cause a loss of 1 million US dollars. Copper and its alloys have excellent seawater corrosion resistance, good electrical and thermal conductivity, and excellent ability to prevent the growth and attachment of marine organisms. Therefore, various types of copper and alloy semi-finished products are widely used in ships and marine engineering, and some uses are irreplaceable. As early as the 17th century, the British Navy used copper to cover wooden ships, which had a good effect in preventing sea maggots from attaching. After the 19th century, iron ships were produced and developed rapidly. Many ocean-going ships of Western countries and the US Navy mostly covered iron ships with copper to achieve the purpose of anti-fouling. In modern times, due to the development of anti-fouling coatings, coating anti-fouling metal materials is no longer the main technology for anti-fouling of the entire ship. However, in certain specific parts, anti-fouling metals still play an important role and have been deeply developed. For example, my country began to study the fouling problem of copper alloys used for propellers in the late 1970s.The antifouling copper alloy for propellers developed by CSIC 725 has a chemical composition of 57~60% Cu, 3~4% Mn, 1.5~2% Fe, 1~2% Al, 0.5~1% Sn, and 0.05~0.1% P. This new copper alloy maintains many advantages of high-strength brass and further improves antifouling and corrosion resistance. The ZCuZn37Sn1 antifouling copper alloy for mine launch antennas, also developed by CSIC 725, has a chemical composition of 64.44% Cu, 0.82% Sn, and the remainder is Zn. The alloy has excellent antifouling properties and has been used in drilling platform lifting sliders, submarine torpedo tube guides, mine launch antennas and other parts with good results. There are currently two views on the mechanism of copper's antifouling performance in seawater. One view is that copper ions produced by the electrochemical dissolution of copper in seawater have an antifouling effect, and only when the corrosion rate of copper or copper alloy is greater than 20μm∙a-1, it has an antifouling effect. Another view is that copper produces a cuprous oxide film on its surface in seawater, which has an antifouling effect. Once the cuprous oxide film is blocked or the composition changes, it loses its antifouling performance. However, these two views cannot explain all copper antifouling phenomena. The antifouling industry generally believes that copper has different critical seepage rates (i.e., the minimum seepage rate that can prevent marine organisms from attaching) for its inhibitory effect on different marine organisms. The critical seepage rate for barnacles is 10μg·cm-2·d-1, for hydras, jellyfish, etc. is 10~20μg·cm-2·d-1, for algae is 20~50μg·cm-2·d-1, and for bacterial mucous membranes is 40μg·cm-2·d-1. From the data, it can be seen that copper has an antifouling effect on most marine organisms and has a broad spectrum. This can explain the anti-fouling property of pure copper, but it does not apply to some copper alloys. For example, brass has a strong tendency to dezincify in seawater. Although its corrosion rate can reach 30μm∙a-1, the dissolved zinc accounts for the majority, and the copper seepage rate is not high, so it has no anti-fouling effect. Summary of the invention
[0008] The purpose of the present invention is to provide a multi-mechanism synergistic anti-corrosion and anti-fouling composite protective film structure to solve the problem that the hull and the seabed door are painted with anti-fouling paint at the same time, but when there is no biological attachment on the hull, the paint on the seabed door has become ineffective and has been covered with marine organisms, which will cause the seabed door to be blocked, reduce water flow, affect the ship's cooling system, and create safety hazards. Another problem is that the construction of anti-fouling paint is relatively complicated and cumbersome, which is not conducive to use in emergency applications such as quick repairs.
[0009] The technical solution adopted by the present invention to solve the technical problem is: a multi-mechanism synergistic anti-corrosion and anti-fouling composite protective film structure, comprising a copper and its alloy layer, a polymer composite material layer and an adhesive layer, wherein the copper and its alloy layer comprises the following components by mass percentage: 62-70% copper powder; 20-25% Cu2O powder; 3-4% Mn; 1-2% Al; 0.5-1% Sn; 0.05-0.1% P; the mixing method is ball milling, and the parameters of ball milling include: ball-to-material mass ratio of 5-8, speed ratio of 1:2, revolution speed of 300-400rpm, rotation speed of 600-800rpm, and time of 10-15 hours; and then crushing and sieving to obtain the copper and its alloy powder; The materials of the polymer composite material layer are mixed in a mixer according to weight percentage, and 55% to 70% of PET and 0.5% to 0.8% of coupling agent are added in sequence, and then 0.2% to 0.6% of antioxidant, 1% to 3% of lubricant, and 0.2% to 0.6% of nucleating agent are added in sequence to obtain a first mixture; the first mixture is mixed with a reinforcing agent in a ratio of 30% to 50% drawn in through a side inlet of an extruder to obtain a second mixture; the second mixture is extruded and pelletized through an extruder to obtain a polymer composite material; The adhesive layer is composed of rubber toughened epoxy adhesive, which is fully coated by precision coating. The coating thickness of the adhesive layer after drying is 15-20 microns.
[0010] The PET is a pure PET resin with medium viscosity; the PET is a pure PET resin with medium viscosity; the PET is a glossy pure PET resin; the intrinsic viscosity of the PET is 0.65-0.68 dl / g; the reinforcing agent is glass fiber or other fibers.
[0011] The coupling agent is a silane coupling agent, and the coupling agent is 3-aminopropyltriethoxysilane; The antioxidant is a compound antioxidant of antioxidant 1010 and antioxidant 168 in a ratio of 1:1; The lubricant is silicone powder; The nucleating agent is a 00s nucleating agent.
[0012] The extruder is a twin-screw extruder, wherein the temperature between the feed port and the die head of the twin-screw extruder can be divided into two zones, the feed port temperature is 320°C, the temperature of zone one is 335°C, and the temperature of zone two is 340°C.
[0013] The composite process of the three layers of copper and its alloy layer, polymer composite material layer and bonding layer is as follows: the bonding layer is covered on the polymer composite material layer by coating, and the copper and its alloy layer is coated on the polymer composite material layer by ultra-high pressure powder impact equipment, wherein the powder temperature is 40-50 degrees, the air pressure is 7-10Mpa, and the working distance is 15-25mm.
[0014] The beneficial effects of the present invention are as follows: 1. The copper-based zero-permeation protective composite film does not contain any solvent and will not pollute the marine environment, and is an environmentally friendly protective material. 2. The copper-based zero-permeation protective composite film uses the characteristics of copper to effectively prevent microbial attachment and has a long protection time. 3. The copper-based zero-permeation protective composite film has strong adhesion, high strength, and high elasticity, and can prevent water flow, collision, and other factors from falling off. It is particularly suitable for deep-sea hydrostatic pressure and high-pressure water and corrosive ion penetration environments. 4. The copper-based zero-permeation protective composite film has good weather resistance, can adapt to the changing marine environment, can be used under harsh conditions, has strong resistance to seawater corrosion, and has a long anti-corrosion life. It can generally be used for more than 10 or 15 years, even in acid, alkali, salt and solvent media, and under certain temperature conditions, it can also be used for more than 5 years. The corrosion resistance salt spray test time can reach 5,000 hours, and the anti-corrosion cycle is particularly long. This product is made of in-situ composite of copper alloy and polymer materials. Compared with conventional anti-corrosion coatings, it has improved mechanical strength and toughness, wear resistance, hydrophobic antifouling and anti-microbial properties. It has the advantages of stronger adhesion, high hardness, wear resistance and impact resistance, and long acid and alkali aging resistance.
[0015] The present invention will be described in more detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The hull and seabed door areas are covered with marine life pictures.
[0017] Figure 2 It is a schematic diagram of the structure of the present invention.
[0018] Figure 3 This is a state effect diagram of the present invention.
[0019] In the figure: 1. Copper and its alloy layer, 2. Polymer composite material layer, 3. Adhesive layer. DETAILED DESCRIPTION
[0020] The directions or positional relationships indicated by the terms "upper", "lower", "inner", "outer", "front end", "rear end", "two ends", "one end", "the other end" and the like in the application text are based on the directions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the devices or elements referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.
[0021] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "provided with", "connected", etc. should be understood in a broad sense. For example, "connected" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0022] Embodiment 1, as Figure 1 , 2 As shown, a multi-mechanism synergistic anti-corrosion and anti-fouling composite protective film structure comprises a copper and its alloy layer 1, a polymer composite material layer 2 and an adhesive layer 3, wherein the copper and its alloy layer comprises the following components by mass percentage: copper powder 62-70%; Cu2O powder 20-25%; Mn 3-4%; Al 1-2%; Sn 0.5-1%; P 0.05-0.1%; the mixing method is ball milling, and the parameters of ball milling include: ball-to-material mass ratio of 5-8, speed ratio of 1:2, revolution speed of 300-400rpm, rotation speed of 600-800rpm, and time of 10-15 hours; and then crushing and sieving to obtain the copper and its alloy powder; The materials of the polymer composite material layer are mixed in a mixer according to weight percentage, and 55% to 70% of PET and 0.5% to 0.8% of coupling agent are added in sequence, and then 0.2% to 0.6% of antioxidant, 1% to 3% of lubricant, and 0.2% to 0.6% of nucleating agent are added in sequence to obtain a first mixture; the first mixture is mixed with a reinforcing agent in a ratio of 30% to 50% drawn in through a side inlet of an extruder to obtain a second mixture; the second mixture is extruded and pelletized through an extruder to obtain a polymer composite material; The adhesive layer is composed of rubber toughened epoxy adhesive, which is fully coated by precision coating. The coating thickness of the adhesive layer after drying is 15-20 microns.
[0023] The PET is a pure PET resin with medium viscosity; the PET is a pure PET resin with medium viscosity; the PET is a glossy pure PET resin; the intrinsic viscosity of the PET is 0.65-0.68 dl / g; the reinforcing agent is glass fiber or other fibers.
[0024] The coupling agent is a silane coupling agent, and the coupling agent is 3-aminopropyltriethoxysilane; The antioxidant is a compound antioxidant of antioxidant 1010 and antioxidant 168 in a ratio of 1:1; The lubricant is silicone powder; The nucleating agent is a 00s nucleating agent.
[0025] The extruder is a twin-screw extruder, wherein the temperature between the feed port and the die head of the twin-screw extruder can be divided into two zones, the feed port temperature is 320°C, the temperature of zone one is 335°C, and the temperature of zone two is 340°C.
[0026] The composite process of the three layers of copper and its alloy layer, polymer composite material layer and bonding layer is as follows: the bonding layer is covered on the polymer composite material layer by coating, and the copper and its alloy layer is coated on the polymer composite material layer by ultra-high pressure powder impact equipment, wherein the powder temperature is 40-50 degrees, the air pressure is 7-10Mpa, and the working distance is 15-25mm.
[0027] This product utilizes the excellent seawater corrosion and microbial fouling resistance of copper alloy. At the same time, the polymer film material is closely attached to the surface of the substrate to form a barrier layer that can block oxygen and prevent the penetration of water molecules and other corrosive ions, providing effective protection for the substrate. The copper-based zero-permeability protective composite film can be flexibly arranged on the outer shell of equipment of different shapes, and can be completed by directly pasting the film, which is convenient for application and construction.
[0028] Preliminary test results: Laboratory evaluation of the protective film material and marine hanging board testing were carried out based on limited conditions. The test results show that the multi-mechanism synergistic anti-corrosion and anti-fouling polymer protective film has excellent antibacterial and anti-fouling properties. It is an environmentally friendly, broad-spectrum new type of anti-corrosion and anti-fouling material for marine equipment. It brings new inspiration for the long-term dynamic and static anti-fouling strategies for marine equipment. At the same time, it is expected to be applied to anti-fouling fields such as marine engineering equipment, marine ranches, offshore wind power / nuclear power, etc.
[0029] Diatom inhibition experiment: In the natural environment, a biofilm will quickly form on the surface of a submerged object. This film is mainly divided into a bacterial layer and a diatom layer. The presence of the bacterial layer film is conducive to the attachment of diatoms, while the presence of the diatom layer film is conducive to the attachment of large organisms. Diatoms are the main group of marine phytoplankton and the main micro-fouling organisms. Diatoms reproduce by indirect division and usually reproduce without light. Some types of diatoms divide once an hour under suitable conditions, thus forming a group quickly. The diatom gel of the group species extends into a tubular or stalk-shaped body, which is conducive to the direct attachment of diatoms to the submerged object to avoid being washed away by sea water. When diatoms exist in large quantities, they will change the microstructure of the coating and indirectly affect the growth of other mucous membrane organisms. Therefore, diatoms have a vital influence on the formation of the entire biofouling layer. According to laboratory tests, the antifouling film has an inhibitory effect on the attachment of row boat algae, small boat algae, and feather boat algae. The antifouling film has different inhibitory effects on the attachment of three benthic diatoms. The inhibitory effect on Navicula pennata is the most obvious, followed by Navicula spp., and finally Navicula spp. The antifouling film has a persistent and stable inhibitory effect on the attachment of three benthic diatoms. After being immersed in seawater for 45 days, the antifouling film can still produce an inhibition rate of more than 90% on Navicula pennata within 36 hours, and an inhibition rate of more than 85% on Navicula spp. and Navicula spp.
[0030] Preliminary experiments on real sea antifouling: Referring to GB / T5370-2007 "Antifouling paint sample shallow sea immersion test method", the back and sides of the sample were sealed with epoxy putty, leaving only the film-coated part of the test sample exposed. A simple real sea hanging experiment was carried out in the East China Sea, and the experimental results are shown in the figure.
[0031] The effects are: 1. The copper-based zero-permeability protective composite film does not contain any solvents and will not pollute the marine environment. It is an environmentally friendly protective material. 2. The copper-based zero-permeability protective composite film uses the characteristics of copper to effectively prevent microbial attachment and has a long protection time. 3. The copper-based zero-permeability protective composite film has strong adhesion, high strength, and high elasticity, which can prevent water flow, collision, etc. from falling off. It is especially suitable for deep-sea hydrostatic pressure and high-pressure water and corrosive ion penetration environments. 4. The copper-based zero-permeability protective composite film has good weather resistance, can adapt to the changing marine environment, can be used under harsh conditions, has strong resistance to seawater corrosion, and has a long anti-corrosion life. It can generally be used for more than 10 or 15 years. Even in acid, alkali, salt and solvent media, and under certain temperature conditions, it can be used for more than 5 years. The corrosion resistance salt spray test time can reach 5000 hours, and the anti-corrosion cycle is particularly long. This product is made of in-situ composite of copper alloy and polymer materials. Compared with conventional anti-corrosion coatings, it has improved mechanical strength and toughness, wear resistance, hydrophobic antifouling and anti-microbial properties. It has the advantages of stronger adhesion, high hardness, wear resistance and impact resistance, and long acid and alkali aging resistance.
[0032] The above embodiments are merely descriptions of preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary engineering and technical personnel in the field shall fall within the protection scope determined by the claims of the present invention.
[0033] The parts not involved in the present invention are the same as the prior art or can be implemented by using the prior art.
Claims
1. A multi-mechanism synergistic anti-corrosion and anti-fouling composite protective film structure, characterized by: The invention comprises a copper and alloy layer, a polymer composite material layer and an adhesive layer, wherein the copper and alloy layer comprises the following components by mass percentage: 62-70% copper powder; 20-25% Cu2O powder; 3-4% Mn; 1-2% Al; 0.5-1% Sn; and 0.05-0.1% P; the mixing method is ball milling, and the parameters of the ball milling include: a ball-to-material mass ratio of 5-8, a rotation speed ratio of 1:2, a revolution speed of 300-400rpm, a rotation speed of 600-800rpm, and a time of 10-15 hours; and then crushing and sieving to obtain the copper and alloy powder; The materials of the polymer composite material layer are mixed in a mixer according to weight percentage, and 55% to 70% of PET and 0.5% to 0.8% of coupling agent are added in sequence, and then 0.2% to 0.6% of antioxidant, 1% to 3% of lubricant, and 0.2% to 0.6% of nucleating agent are added in sequence to obtain a first mixture; the first mixture is mixed with a reinforcing agent in a ratio of 30% to 50% drawn in through a side inlet of an extruder to obtain a second mixture; the second mixture is extruded and pelletized through an extruder to obtain a polymer composite material; The adhesive layer is composed of rubber toughened epoxy adhesive, which is fully coated by precision coating. The coating thickness of the adhesive layer after drying is 15-20 microns.
2. The multi-mechanism synergistic anti-corrosion and anti-fouling composite protective membrane structure according to claim 1 is characterized by: The PET is a pure PET resin with medium viscosity; the PET is a pure PET resin with medium viscosity; the PET is a glossy pure PET resin; the intrinsic viscosity of the PET is 0.65-0.68 dl / g; the reinforcing agent is glass fiber or other fibers.
3. The multi-mechanism synergistic anti-corrosion and anti-fouling composite protective membrane structure according to claim 1 is characterized by: The coupling agent is a silane coupling agent, and the coupling agent is 3-aminopropyltriethoxysilane; The antioxidant is a compound antioxidant of antioxidant 1010 and antioxidant 168 in a ratio of 1:1; The lubricant is silicone powder; The nucleating agent is a 00s nucleating agent.
4. The multi-mechanism synergistic anti-corrosion and anti-fouling composite protective membrane structure according to claim 1 is characterized by: The extruder is a twin-screw extruder, wherein the temperature between the feed port and the die head of the twin-screw extruder can be divided into two zones, the feed port temperature is 320°C, the temperature of zone one is 335°C, and the temperature of zone two is 340°C.
5. The multi-mechanism synergistic anti-corrosion and anti-fouling composite protective membrane structure according to claim 1 is characterized by: The composite process of the three layers of copper and its alloy layer, polymer composite material layer and bonding layer is as follows: the bonding layer is covered on the polymer composite material layer by coating, and the copper and its alloy layer is coated on the polymer composite material layer by ultra-high pressure powder impact equipment, wherein the powder temperature is 40-50 degrees, the air pressure is 7-10Mpa, and the working distance is 15-25mm.